Về sự hội tụ của một sơ đồ sai phân đối với bài toán biên phi tuyến loại Parabol - Pho, Le Thien (Journal of Computer Science and Cybernetics, 2018)
This paper deals with a finite difference scheme for  a nonlinear boundary problem of  parabolic type. Under the essential assumption about the regularity of the solution of the continuous problem a second order convergence rate O(r2 + h2) is established for approximate solution of the finite difference scheme.